Legal Politics in The Implementation of Legalization Abortion Caused by Rape - Wulandari, Sri (Faculty of Law, Universitas Pekalongan, 2024)
Political power greatly determines the formation of legal rules in realizing people's expectations regarding the enactment of the law. One manifestation of the implementation of legal politics is the enactment of legislation in the context of legalizing abortion due to rape. This research aims to analyze the legalization of abortion as well as efforts to prevent abortion and not vice versa to provide space for abortion which leads to an increase in adulterous behavior by creating a systematic, factual and accurate picture. The research method is normative juridical using secondary and primary data. In positive Indonesian law, abortion is prohibited and is a type of crime. The Health Law and PP on Reproductive Health have a specific objective, namely ensuring the fulfillment of the right to continue life (HAM) and reproductive health through safe, effective and affordable health services, therefore, abortion with indications of a medical emergency and rape are exceptions to the prohibition on abortion.